Evaluation of Risk Factors for Catheter-Related Urinary Tract Infections Caused by Carbapenem-Resistant Klebsiella pneumonia. (4th October 2017) - Ataman Hatipoglu, Cigdem; Bulut, Cemal; Erdinc, Sebnem; Ertem, Gunay; Kinikli, Sami; Tulek, Necla; Dinc, Bedia; Kilic, Esra Kaya; Sonmezer, Meliha Cagla
Abstract: Background: Antimicrobial resistance is an emerging problem. The rate of carbapenem-resistant Klebsiella isolates was progressively increased in recent years. The aim of this study was to evaluate risk factors for catheter-related urinary tract infections (CR-UTI) caused by carbapenem-resistant Klebsiella pneumonia . Methods: In this study, CR-UTIs between January 2014 and April 2017 were evaluated retrospectively. All patients with nosocomial CR-UTI caused by K. pneumonia was included to the study. Only the first isolated K. pneumonia had recorded for each patient. Patients with CR-UTI by CRKP were defined as study group, carbapenem susceptible K. pneumonia as control (CSKP). Comorbidities and risk factors were compared between the two groups. Results: Among 122 patients with CR-UTI caused by K. pneumonia, 66 were female (54%), mean age was 69 ± 20.2 years, mean hospital stay 65.6 ± 54.5 days. Of patients, 93% were followed in intensive care unit (ICU). Mortality rate was 51%, 30 days mortality 66%. Among K. pneumonia isolates, CSKP was detected in 66 patients (%54) and CRKP in 56 patients (46%). ESBL rate was 81%, colistin resistance 16.4%. In CRKP group, ESBL rate was significantly higher than CSKP group (96% vs. 68%) ( P = 0.000) (OR = 12.6, 95% CI: 2.80–56.66). Colistin resistance also was significantly higher in CRKP group (32.1% vs. 5.1%, P = 0.006) (OR = 8.7, 95% CI: 1.71–44.68). Age and gender were not different in the two groups ( P > 0.05). In CRKP group, mortality rate was 3.19 times higher than CSKP group ( P = 0.002), but 30-days mortality was similar ( P > 0.05). Total length of stay in hospital was not different ( P > 0.05) but length of stay in ICU ( P = 0.036) and length of stay before infection ( P = 0.049) was longer in the CRKP group. There was no significant difference in terms of comorbidities ( P > 0.05, for each). In univariate analyses, central venous catheter ( P = 0.044, OR: 2.43, 95% CI: 1.009–5.88) and total parenteral nutrition (TPN) ( P = 0.001, OR: 4.35, 95% CI: 1.83–10.31) were risk factors for CRKP. In multivariate analyses, TPN was found independent risk factor for CRKP ( P = 0.001, OR: 4.88, 95% CI: 1.87–12.72). Conclusion: We detected that mortality rate was higher; length of stay in ICU and length of stay before infection were longer in patients with CR-UTI caused by CRKP. The ESBL rate was also high in CRKP group. TPN was found independent risk factor for acquiring CRKP. Disclosures: All authors: No reported disclosures.